Instrument design and protocol for the study of light controlled processes in aquatic organisms, and its application to examine the effect of infrared light on zebrafish - Dekens, Marcus P. S.; Foulkes, Nicholas S.; Tessmar-Raible, Kristin (PLOS ONE, 2017)
The acquisition of reliable data strongly depends on experimental design. When studying the effects of light on processes such as behaviour and physiology it is crucial to maintain all environmental conditions constant apart from the one under study. Furthermore, the precise values of the environmental factors applied during the experiment should be known. Although seemingly obvious, these conditions are often not met when the effects of light are being studied. Here, we document and discuss the wavelengths and light intensities of natural and artificial light sources. We present standardised experimental protocols together with building plans of a custom made instrument designed to accurately control light and temperature for experiments using fresh water or marine species. Infrared light is commonly used for recording behaviour and in electrophysiological experiments although the properties of fish photoreceptors potentially allow detection into the far red. As an example of our experimental procedure we have applied our protocol and instrument to specifically test the impact of infrared light (840 nm) on the zebrafish circadian clock, which controls many aspects of behaviour, physiology and metabolism. We demonstrate that infrared light does not influence the zebrafish circadian clock. Our results help to provide a solid framework for the future study of light dependent processes in aquatic organisms.
Gesehen am 11.10.2018